Alternative Medical Waste Treatment During COVID-19 Case Study in Hospital X Jakarta City - Dhia Rizki Atthar, Aura; Muitiara Sari, Mega; Wayan Koko Suryawan, I (Universitas Ibn Khaldun Bogor, 2022)
Medical waste management in health care facilities is very important because medical waste has various health risks. One hospital can incur up to Rp 1 billion/year for medical waste treatment costs. This study aims to analyze the proper processing of medical waste in hospitals in Jakarta during the pandemic. This type of research is a descriptive observational study conducted cross-sectional through observations on solid waste management at Hospital X, Jakarta City. Decision analysis in this study uses the Analytical Hierarchy Process (AHP) method to support the medical waste treatment decision-making process. In this study, two processing methods are given, namely the incinerator and autoclave. An incinerator is a thermal process used to treat medical waste at controlled temperatures. An autoclave is a medical waste treatment that combines moisture, heat, and pressure to sterilize medical waste. The results of the AHP show that hospitals should optimize autoclaves to sterilize highly infectious waste, which can also be used to sterilize sharp medical waste. Meanwhile, medical waste treatment using incinerators can generate other waste in the form of ash from combustion residues. Ash from the combustion process can contain heavy metals such as Cr, Zn, and Pb. Therefore, a strategy is needed to deal with this waste generation so that the final treatment does not end in a landfill but can be a useful product.